Selected solutions of environmentally- friendly urban transport systems - Katarzyna Turoń; Grzegorz Sierpiński (Economic and Environmental Studies (E&ES), 2019)
The article is related to urban transport systems. The authors focus on solutions that will positively influence the problem of excessive noise or pollution generated in cities through transport activities. They refer to existing single initiatives, but also demonstrate the need for complex solutions that integrate solutions into a single system that enables the use of various means of transport through organizational and ICT solutions. The aim of the article was to present a review of selected solutions that could reduce the harmful effects of transport, which can be used to improve the environmental performance of urban transport systems.
Keywords: R41; R42; 330; public transportation; public transport; bike-sharing; car-sharing; eco-mobility; electro-mobility; mobility; sustainable development of transport; ICT